Pengaruh Kesadaran Merek dan Citra Merek Terhadap Loyalitas Pelanggan dengan Kepercayaan Merek Sebagai Variabel Intervening (Studi pada Pelanggan Teh Pucuk Harum Wilayah Surabaya Utara) - CHUSNIARTININGSIH, EKA; LESTARI ANDJARWATI, ANIK (Jurnal Ilmu Manajemen (JIM), 2018)
The purpose of this study is to examine and analyze the effect of brand awareness and brand image to customer loyalty with brand trust as intervening variable on customer of Teh Pucuk Harum. This research is a causality research with quantitative approach. Technique of sampling using non probability sampling with amount 220 respondents in North Surabaya. Statistical analysis in this study is path analysis with the help of AMOS 22.0 version software. The results of this study explain that a significant influence of brand awareness on brand trust, brand image on brand trust, brand trust on customer loyalty, brand awareness on customer loyalty and no significant influence of brand image to customer loyalty. Keywords: brand awareness, brand image, brand trust, and customer loyalty.